Management Skils and Marketing Strategy on Business Success of Songket Weaving Fabric of Sasak Lombok - Mispandi, Mispandi; Wijaya, Lalau Hendra; Fahrurrozi, Muh; Nnamdi Ogbolu, Anthony (Sumber Belajar Sejahtera, 2024)
This study aims to analyze and describe the effect of management capabilities and marketing strategies on business success. This type of research is quantitative. This research was conducted in the village of voluntary and the village of Rembitan, Central Lombok district, which became the subject of this study. The sample in this study was 300 respondents who are woven cloth entrepreneurs. The data collection technique is done using a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression. The results of this study indicate that: (1) management ability has a positive and significant effect on the success of the songket woven fabric business by 37.3% with a significance value (p) <0.05. (2) Marketing strategy has a positive and significant effect on business success by 38.7% with a significance value (p) <0.05